2011
DOI: 10.1021/ma2013755
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring in Real-Time the Degrafting of Covalently Attached Fluorescent Polymer Brushes Grafted to Silica Substrates—Effects of pH and Salt

Abstract: Polymer-bearing surfaces are of particular interest because of their thermal and solvent response, 1,2 their prospective use as protein and cell adhesive platforms, 3À5 or as self-biolubricating substrates, among others. 6 Surface-tethered polymer chains provide the means to tailor the surface properties by undergoing externally stimulated conformational changes. This is particularly true for polyelectrolyte polymers such as poly(acrylic acid) (PAA) whose degree of ionization is highly influenced by pH, ionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 55 publications
0
52
0
Order By: Relevance
“…18 In the case of polyelectrolytes, pH-induced swelling can produce sufficient tension to activate the grafting chemistry for hydrolysis. 12,15,17,19 The σ of a polymer brush can also generate tension. At low σ, when the distance between neighboring chains (d) is much greater than the gyration radius of the grafted chains (R g ), the grafted chains will adopt a Gaussian conformation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In the case of polyelectrolytes, pH-induced swelling can produce sufficient tension to activate the grafting chemistry for hydrolysis. 12,15,17,19 The σ of a polymer brush can also generate tension. At low σ, when the distance between neighboring chains (d) is much greater than the gyration radius of the grafted chains (R g ), the grafted chains will adopt a Gaussian conformation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For the surface-grafted initiator commonly employed with silicon substrates, [11-(2-bromo-2-methyl)-propionyloxy] undecyltrichlorosilane (eBMPUS), shown in Figure 1b, two possible functional groups are liable to breakage due to hydrolysis: (1) the siloxane networks at the initiator/ substrate interface and/or (2) the ester group contained within the initiator. While some researchers have identified siloxane linkage cleavage in replacement reactions in silane monolayers 20 and as the point of scission in brush systems, 13,15 there is a possibility that the ester in the initiator can also be activated for and undergo hydrolysis. 12,18,21,22 Regardless of the bond that undergoes hydrolysis and leads to degrafting of the polymer from the surface, one testable hypothesis that arises from this mechanism is that a weak polyacid (e.g., poly(methacrylic acid), PMAA) will exhibit increasing levels of instability with increasing pH.…”
Section: ■ Introductionmentioning
confidence: 99%
“…End anchoring of polymer chains at a high density to a surface to form polymer brushes is a powerful way to prepare functional coatings . Fluorescent dye‐labeled polymer brushes have been prepared and utilized in ion sensing and organic light emitting diode (OLED) development or in studying the degrafting kinetics of brushes . In this context, responsive polymer brushes, which undergo conformational change upon certain, for example, pH, temperature, ionic strength, and solvent have been modified with fluorescent probes and widely used in the design of sensors .…”
Section: Introductionmentioning
confidence: 99%
“…To date, most fluorescently labeled polymer brushes have been prepared by functionalizing side chains with dye molecules as a post‐polymerization step, by copolymerization with a fluorescent monomer or by self‐assembly of charged fluorescent molecules on charged polymer brushes by electrostatic interactions . One disadvantage of these techniques is that physicochemical properties of the system such as swelling, crystallinity, or wettability are strongly altered by the introduction of a dye, which limits the applicability.…”
Section: Introductionmentioning
confidence: 99%
“…The substrate‐organic molecule linkage (SiC) is strong enough for both supporting the reaction conditions necessary for living radical polymerization methods and subsequent polymer brush formation and characterization. Recently, Giasson and coworkers reported that poly(acrylic acid) brushes built on mica by tethering polystyrene‐poly(acrylic acid) diblock copolymers in a polystyrene layer covalently linked to OH‐activated mica surfaces resist to cleavage at pH 5.5 with added NaCl for several days. They also investigated effects pH and salt on the detaching resist to cleavage of covalently attached fluorescent poly(acrylic acid) brushes grafted to silicon substrate.…”
Section: Introductionmentioning
confidence: 99%